2008
DOI: 10.1210/en.2007-1694
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Gqin the Hypertrophic Signal Transduction of Angiotensin II in Vascular Smooth Muscle Cells

Abstract: The angiotensin II (AngII) type 1 receptor (AT(1)) plays a critical role in hypertrophy of vascular smooth muscle cells (VSMCs). Although it is well known that G(q) is the major G protein activated by the AT(1) receptor, the requirement of G(q) for AngII-induced VSMC hypertrophy remains unclear. By using cultured VSMCs, this study examined the requirement of G(q) for the epidermal growth factor receptor (EGFR) pathway, the Rho-kinase (ROCK) pathway, and subsequent hypertrophy. AngII-induced intracellular Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 48 publications
5
57
0
Order By: Relevance
“…Although surrogate growth markers can be stimulated without G-protein coupling, we report that G-protein coupling is crucial at the cardiomyocyte level for hypertrophy, consistent with a recent study in vascular smooth muscle cells. 13 Moreover, AT 1 R G-protein coupling is sufficient to trigger cardiomyocyte hypertrophy, as seen with [N111G]AT 1A R. This observation is consistent with a recent knock-in study using N111S/⌬329 AT 1 R, which found that mice had significantly larger heart weight/body weight ratios and elevated brain natriuretic peptide levels, although the more profound phenotype was that of hypertension and cardiac fibrosis. 34 Although G␣ q/11 is the obvious candidate for mediating the G protein-dependent effects described herein, it is important to note that other G-protein subunits can be activated by the AT 1 R in both cardiomyocytes and vascular smooth muscle cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although surrogate growth markers can be stimulated without G-protein coupling, we report that G-protein coupling is crucial at the cardiomyocyte level for hypertrophy, consistent with a recent study in vascular smooth muscle cells. 13 Moreover, AT 1 R G-protein coupling is sufficient to trigger cardiomyocyte hypertrophy, as seen with [N111G]AT 1A R. This observation is consistent with a recent knock-in study using N111S/⌬329 AT 1 R, which found that mice had significantly larger heart weight/body weight ratios and elevated brain natriuretic peptide levels, although the more profound phenotype was that of hypertension and cardiac fibrosis. 34 Although G␣ q/11 is the obvious candidate for mediating the G protein-dependent effects described herein, it is important to note that other G-protein subunits can be activated by the AT 1 R in both cardiomyocytes and vascular smooth muscle cells.…”
Section: Discussionsupporting
confidence: 86%
“…10 Indeed, others indicate that G-protein coupling to AT 1 R is required for EGFR transactivation in COS-7 and vascular smooth muscle cells. [11][12][13] Meanwhile, evidence for ␤-arrestin-dependent functional selectivity of the Ang II analog sarcosine, 1 isoleucine, 4 isoleucine, 8 Ang II (SII Ang II), 14 ␤-arrestin-mediated EGFR transactivation by ␤ 1 -adrenoceptors independent of G-protein coupling, 15 and the very recent demonstration of ␤-arrestin-dependent hypertrophy resulting from mechanical stretch 16 suggests that ␤-arrestin scaffolding of extracellular signal-regulated kinase (ERK) 1/2 may contribute to transactivation and/or cardiac hypertrophy.…”
mentioning
confidence: 99%
“…Additionally, these cells were selected for their functional relevance, where AT 1 R overexpression has been implicated in breast cancer pathogenesis (De Paepe et al, 2001;Rhodes et al, 2009;Tahmasebi et al, 2006). Furthermore, AT 1 R-EGFR transactivation could be modulated by siRNA knockdown of either the AT 1 R or EGFR as well as by targeting G q/11 , an absolute requirement for AT 1 R-EGFR transactivation in other cell types, including cultured cardiomyocytes (Smith et al, 2011) and vascular smooth muscle cells (VSMC) (Mifune et al, 2005;Ohtsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The classical Gαq signalling pathway activated by AT 1 R is shown in Figure 1.1 (Dr. Hsiu-Wei Chan, PhD thesis): AT 1 R interacts with the Gq protein leading to the activation of protein kinase C (PKC) and mobilization of Ca 2+ from intracellular stores. The activated PKC and mobilized Ca 2+ trigger individual downstream signalling pathways (Ohtsu et al, 2008). PKC is a critical kinase that regulates multiple cellular activities such as cell proliferation, survival and apoptosis.…”
Section: Ang II Induces Cardiomyocyte Hypertrophymentioning
confidence: 99%
“…In the first step of this process, Ang II binding to the AT 1 R triggers Gq signalling (Ohtsu et al, 2008), which in turn activates PKC and Ca 2+ signalling. Both PKC and Ca 2+ can potentially contribute to triggering the next step in the TMPS pathway.…”
Section: Potential Mechanisms For Erbb1 Transactivation By Ang Ii: Thmentioning
confidence: 99%